Biodiversity and Habitat Characteristics of the Bycatch Assemblages in Fish Aggregating Devices (FADs) and School Sets in the Eastern Pacific Ocean - Lezama-Ochoa, Nerea; Murua, Hilario; Hall, Martin; Román, Marlon; Ruiz, Jon; Vogel, Nick; Caballero, Ainhoa; Sancristobal, Igor (Frontiers in Marine Science, 2017)
This study examined diversity and habitat characteristics for bycatch assemblages in two different types of fishing (drifting fish aggregating devices sets and sets made on school of tunas) in the eastern Pacific Ocean (20ºS-30ºN and 70º-150ºW) between 2005 and 2011 using biodiversity metrics and Generalized Additive Models. Bycatch information was based on data collected by onboard observers covering more than 80% of the purse seine fishing trips. Our results suggest that diversity and habitat characteristics of the bycatch assemblages differ depending of the fishing mode. Thus, diversity was mostly explained by area and set type; being higher in FAD sets than School sets. Concretely, diversity seems to be directly related with the equatorial upwelling and the front system in FAD sets and with the Costa Rica Dome and the coastal upwelling of Panama induced by wind jets in School sets. Among environmental variables, temperature and chlorophyll were the most important predictors to describe the diversity of the bycatch assemblages. This work has investigated multiple indicators related to the bycatch assemblages and their habitat, which could be helpful for the development of an Ecosystem Approach to Fishery Management.